Parasympathetic and sympathetic activity are associated with individual differences in neural indices of selective attention in adults. (6th April 2018) - Giuliano, Ryan J.; Karns, Christina M.; Bell, Theodore A.; Petersen, Seth; Skowron, Elizabeth A.; Neville, Helen J.; Pakulak, Eric
Abstract: Multiple theoretical frameworks posit that interactions between the autonomic nervous system and higher‐order neural networks are crucial for cognitive and emotion regulation. However, few studies have directly examined the relationship between measures of autonomic physiology and brain activity during cognitive tasks, and fewer studies have examined both the parasympathetic and sympathetic autonomic branches when doing so. Here, 93 adults completed an ERP auditory selective attention task concurrently with measures of parasympathetic activity (high‐frequency heart rate variability; HF‐HRV) and sympathetic activity (preejection period; PEP). We focus on the well‐studied N1 ERP component to test for associations with baseline values of HF‐HRV and PEP. Individuals with higher resting HF‐HRV and shorter resting PEP showed larger effects of selective attention on their ERPs. Follow‐up regression models demonstrated that HF‐HRV and PEP accounted for unique variance in selective attention effects on N1 mean amplitude. These results are consistent with the neurovisceral integration model, such that greater parasympathetic activity is a marker of increased selective attention, as well as other theoretical models that emphasize the role of heightened sympathetic activity in more efficient attention‐related processing. The present findings highlight the importance of autonomic physiology in the study of individual differences in neurocognitive function and, given the foundational role of selective attention across cognitive domains, suggest that both parasympathetic and sympathetic activity may be key to understanding variability in brain function across a variety of cognitive tasks.